DIFFERENCES BETWEEN TABOOS AND STEREOTYPES ACROSS COUNTRIES: A CROSS-CULTURAL ANALYSIS - Mengto'rayeva Shodiya Hamidulla qizi; Xudoyberdiyeva Laylo Abdumalik Qizi; Qurbonova Gulzira Olimovna (TADQIQOTLAR, 2025)
Taboos  and  stereotypes  are  integral  components  of  cultural  frameworks  that shape  social  interactions  and  perceptions  worldwide.  While  taboos  represent prohibitions rooted in cultural, religious, or moral beliefs, stereotypes are generalized assumptions about groups based on perceived characteristics. This article examines the distinctions  between  taboos  and  stereotypes,  their  manifestations  across  various countries, and their implications for intercultural communication. Using a comparative approach, we analyze examples from diverse cultural contexts, including China, India, the  United  States,  and  Saudi  Arabia,  to  highlight  how  these  phenomena  influence behavior  and  societal  norms.  The  findings  underscore  the  importance  of  cultural sensitivity in navigating global interactions and suggest strategies for fostering mutual understanding.